Energetic and exergetic performance analysis of CdS/CdTe based photovoltaic technology in real operating conditions of composite climate. (15th February 2016) - Rawat, Rahul; Kaushik, S.C.; Sastry, O.S.; Singh, Y.K.; Bora, B.
Highlights: Performance analysis of 3.2 kWP CdTe PV system has been carried out. Performance ratio and thermodynamic efficiencies have been determined. Electrical parameters have been assessed at alternative reporting conditions. Exergy analysis of the system has been carried out. Degradation rate of the system has been calculated to be 0.18%/year. Abstract: The solar photovoltaic (PV) technology market has increased rapidly with the continuously increasing electricity demand and climate concerns. With the increased PV installed capacity, the performance analysis of these systems has become critically important in order to ensure its reliable operation for a long lifetime, monetary payback and to identify the scope of improvement. The well-established conventional energetic performance analysis techniques are quantitative approaches based on energy conservation while the exergetic performance analysis is the qualitative method which is based on second law of thermodynamics. In this paper, an approach for energetic and exergetic performance analysis has been developed so as to determine the long term performance of PV systems in real operating conditions. A methodology has been proposed for utilizing the long term time series outdoor data in order to assess the performance of PV system statistically and to determine the system degradation rate. The degradation rate of 3.2 kWP CdTe PV system is found to be 0.18% per year after 23 months of operation in composite climate which is lower than the reported degradation rate of earlier CdTe technology. The average performance ratio (PR), energetic and exergetic efficiency of the system is found to be 0.89%, 9.84% and 10.62% respectively. The average exergetic efficiency is found to be increased by 12% by utilizing the recoverable thermal exergy loss in photovoltaic-thermal system. The instantaneous PR of 93.5% of the per minute data is found to be in the range of 0.84–0.95. Additionally, the electrical parameters have been translated to standard test conditions so as to evaluate the system with respect to the rated capacity.